Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.ekir.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Renal Function and Hemodialysis Treatment on Plasma Vasopressin and Copeptin Levels

Abstract: IntroductionCopeptin is increasingly used in epidemiological studies as a substitute for vasopressin. The effect of renal function per se on copeptin and vasopressin concentrations as well as their ratio have, however, not been well described.MethodsCopeptin and vasopressin levels were measured in 127 patients with various stages of chronic kidney disease, including 42 hemodialysis patients and 16 healthy participants in this observational study. Linear (segmental) regression analyses were performed to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 37 publications
(52 reference statements)
2
19
0
1
Order By: Relevance
“…Our study showed positive correlation between plasma osmolality and copeptin in the group of nondialyzed CKD5 patients, whereas such relationship was not observed in PD and HD groups, and nondialyzed patients had also lower plasma copeptin levels than the other two groups. This accords with Ettema et al [32] who examined copeptin levels in patients with different stages of CKD, including CKD5. They observed positive correlation between plasma osmolality and copeptin in patients with CKD and higher residual renal function (RRF) associated with lower plasma copeptin levels in HD patients which underscore the importance of RRF in the clearance of copeptin.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study showed positive correlation between plasma osmolality and copeptin in the group of nondialyzed CKD5 patients, whereas such relationship was not observed in PD and HD groups, and nondialyzed patients had also lower plasma copeptin levels than the other two groups. This accords with Ettema et al [32] who examined copeptin levels in patients with different stages of CKD, including CKD5. They observed positive correlation between plasma osmolality and copeptin in patients with CKD and higher residual renal function (RRF) associated with lower plasma copeptin levels in HD patients which underscore the importance of RRF in the clearance of copeptin.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, although the circulating concentration of copeptin directly reflects that of AVP and copeptin shows the same response to osmotic changes as AVP in CKD, copeptin is reported to increase more than vasopressin suggesting that the clearance rate of copeptin is more markedly reduced than for vasopressin when GFR decreases. Thus, while copeptin reflects vasopressin levels, in CKD stages 4 and 5, a correction for renal function might be required [14,32].…”
Section: Discussionmentioning
confidence: 99%
“…Although their plasma concentrations correlate over a wide range of plasma and/or urine osmolalities, the strength of the correlation might vary with the GFR (14). However, the correlation seems relatively stable for eGFR > 30 ml/min/1.73 m 2 (43), which corresponds to all but 8 of the participants in…”
Section: Discussionmentioning
confidence: 95%
“…Both vasopressin and copeptin are small-sized molecules and thus could be subjected to renal clearance. However, results from a recent investigation suggest that renal clearance is not the predominant factor in the degradation of circulating copeptin (43). Moreover, strong experimental data have been accumulated in the last decades supporting a direct causal role for vasopressin in the pathogenesis of CKD (15).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…Copeptin correlates well with vasopressin levels and can be measured reliably in plasma over a wide range of physiological changes in plasma osmolality [25][26][27] viduals with estimated glomerular filtration rate (eGFR) >28 mL/min/1.73 m 2 . A correction for renal function may be required below this level of eGFR [28].…”
Section: Vasopressin and Copeptinmentioning
confidence: 99%